Dihydrojasmone from antifungal bacterial endophytes as a biocontrol agent against leaf spot pathogens threatening the endangered Tertiary relict plant Parrotia subaequalis - Yang, Mingmei; Liu, Xingjian; Zhu, Wenhao; Quan, Zhanghua; Shen, Jiahao; Wang, Ren; Zhou, Jiayu (Frontiers in Plant Science, 2025)
IntroductionParrotia subaequalis, an endangered Tertiary relict species endemic to eastern China, holds significant values for both evolutionary ecology and ornamental horticulture. However, it is increasingly threatened by leaf spot disease. The causal pathogens and the potential role of bacterial endophytes in disease suppression remain uncharacterized.MethodsIn this study, fungal pathogens were isolated from diseased leaves collected from native habitats and their pathogenicity was confirmed by Koch’s postulates. Simultaneously, bacterial endophytes were isolated from the non-lesioned portions of diseased leaves and screened for their antagonistic activity. Additionally, the antifungal potential of bacterial secondary metabolites was evaluated and analyzed using untargeted metabolomic profiling.ResultsFour fungal strains, Alternaria sp. S1, Schizophyllum sp. S2, Diaporthe sp. S5, and Botryosphaeria sp. S6, were confirmed as causal agents of leaf spot disease, with S5 causing the most severe symptoms. A total of 206 bacterial endophytes were isolated and 25 strains exhibited strong inhibition against fungal pathogens. Among them, Bacillus species showed the strongest antagonistic effects. Additionally, there were 103 bacterial metabolites identified. Seven abundant metabolites were tested for their antifungal activity, revealing that dihydrojasmone (DJ) and δ-tridecalactone (DT) significantly inhibited fungal growth. DJ displayed broad-spectrum inhibition, suppressed fungal melanin synthesis, and induced hyphal deformation, while DT exerted weaker but significant effects against S2 and S6.DiscussionThis study provides the first identification of fungal pathogens responsible for leaf spot disease in P. subaequalis. The strong antifungal activities of endophytic Bacillus species and their metabolites were demonstrated, highlighting their promise as eco-friendly biocontrol agents.